A pedagogical alliance for academic achievement: Socio-Emotional effects on assessment outcomes. Issue 1 (2nd January 2018) - Leighton, Jacqueline P; Guo, Qi; Chu, Man-Wai; Tang, Wei
ABSTRACT: Assessment of student learning outcomes is often discussed in relation to curriculum, standards and even administration practices. However, assessment of learning outcomes is rarely discussed in light of students' socio-emotional contexts, which might help or hinder learning outcomes. For example, do students' perceptions of the teacher as trustworthy influence their empathic views on classmates, learning engagement, academic achievement and wellbeing? The present paper reports the results of a theoretically-driven, short-term longitudinal study designed to explore the effects of socio-emotional variables, specifically students' trust in teachers and empathy towards self and peers on engagement for learning, academic achievement, and wellbeing. Grounded in attachment theory and the LEAFF model, Panel Structural Equation Modeling (P-SEM) results revealed three significant pathways, which provide evidence that student trust in teachers may serve to launch a domino effect of outcomes, predicting students' empathic views of classmates, learning engagement, academic achievement, and wellbeing.